A fuzzy pert approach to evaluate plant construction project scheduling risk under uncertain resources capacity - Hsian Jong Hsiau; Chun Wei R. Lin (Journal of Industrial Engineering and Management (JIEM), 2009)
A plant construction project always involves lots of activities. Precise information about the activities duration is unfortunately unavailable due to the uncertain resources capacity. The fuzzy program evaluation and review technique (PERT) has been widely applied to solve the fuzzy project scheduling problem. This paper presents an extended fuzzy PERT approach with four major improvement aspects to support the construction project scheduling management: 1) Evaluate operation fuzzy times based on available working volumes, resources quantity and fuzzy capacity of resources, 2) Adopting a maximal alpha_i-level cut method to compare the fuzzy precedent activities times to determine the reasonable earliest starting times of each activity, 3) Using fuzzy algebra method instead of fuzzy subtraction method to compute the fuzzy latest starting times and 4) Developing a project scheduling risk index (PSRI) to assist the decision maker to evaluate the project scheduling risk. Simulations experiments are conducted and demonstrated satisfactory results.
Keywords: 650; Fuzzy PERT approach; project scheduling; construction project; project management